Utilization of borax production waste in zinc (Zn+2) adsorption from industrial wastewater - Dumanli, F. Tugce Senberber; Rona, Esma B.; Ozen, Meral Yildirim; Derun, Emek Moroydor (TAYLOR & FRANCIS LTD, 2025)
Borax production waste materials were determined as a possible adsorbent to eliminate the zinc (Zn+2) concentration in industrial wastewater. To investigate the adsorption mechanism, reaction parameters were optimized such as solution pH, dilution ratio (initial concentration) and contact time. The effect of pH had a vital role on the adsorption efficiency. The optimum solution pH was selected as 9 and contact time was selected as 90 mins. In the isothermal and kinetic modeling, Temkin isotherm (R2: 0.9851) and Lagergren pseudo-second-order kinetic method (R2: 0.9999 - 9.9945) were determined as the best fitted functions. The results indicated the weak interaction between molecules of adsorbent and adsorbate that related to the physical adsorption. Rate constants of k2 were found between -16.5017 and 48.7805 whereas the values of qe were estimated in the range of 49.5050 and 96.1538 for the different dilution ratios. The results also proved that industrial wastes can be an option for water treatment processes.
Keywords: Adsorption; borax waste; kinetic; zinc; isotherm; wastewater; AQUEOUS-SOLUTION; FLY-ASH; REMOVAL; EQUILIBRIUM; KINETICS; MECHANISMS; CARBON; COPPER; Environmental Sciences & Ecology; Toxicology